A Four-Step Process to Assess the Fiscal Performance and Sufficiency of State Road Funds: An Application to Kentucky. (July 2015) - Gibson, Bryan; Denison, Dwight; Wallace, Candice; Kreis, Doug
Aging transportation infrastructure and diminishing financial resources are challenging the management of state transportation systems. Policy makers and administrators are seeking fiscal performance measurement tools to better monitor and manage infrastructure. This article discusses and applies a four-step process to examine past revenue and expenditure trends to determine transportation expenditure sufficiency for state road funds, using the Kentucky Road Fund as a template. A comprehensive approach to this issue is utilized by demonstrating several possible measures of sufficiency and then presenting some future scenarios. Expenditures across various facets of the transportation system are then analyzed with a number of performance metrics as well as construction cost measures to estimate sufficiency. Finally, short-term forecasts of several revenue scenarios are presented to provide context for possible future funding levels under the current revenue regime. The Kentucky case study provides a template to analyze state road funds and potentially draw conclusions as to the continued solvency and state of transportation infrastructure. As policy makers better understand the sufficiency of road fund resources to meet transportation priorities, they will better understand the costs of meeting future transportation needs and the opportunity costs of diverting transportation resources to other policy priorities.